Theory of Microwell Arrays Performing as Generators–Collectors Based on a Single Bipolar Plane Electrode. Issue 3 (4th September 2015) - Oleinick, Alexander; Yan, Jiawei; Mao, Bingwei; Svir, Irina; Amatore, Christian
Abstract: Electroanalytical arrays of microwells with increased sensitivity and virtual immunity to interferents have been previously reported by us. Such arrays were designed to be operated in a classical generator–collector mode but exhibited also similar properties when their common planar collector was left floating. This evidenced that the unbiased collector acted as a bipolar electrode. In this work, a theory is elaborated to investigate in great detail the generality of this phenomenon and its limits. This establishes that if the analyte pertains to a redox couple with relatively fast electron rate constants, the bipolar collector results to be almost as efficient as when biased, thus suppressing the need for a bi‐potentiostat with obvious gain for analytical applications. Conversely, if the analyte rate constant of electron transfer is small, efficient operation in a bipolar mode remains feasible but requires a drastic decrease of the microwell density in the array. Abstract : Unbiased and efficient : Plane‐recessed disk‐electrode arrays are extremely useful for sensing purposes, even when the top‐plane electrode is not biased. This theoretical study provides insights into the bipolar performance of such systems and shows that rational design may allow their optimization for a broad range of experimental conditions.